Novel cyclodextrin-based pH-sensitive supramolecular host–guest assembly for staining acidic cellular organelles. Issue 8 (23rd November 2017) - Pricope, Gabriela; Ursu, Elena Laura; Sardaru, Monica; Cojocaru, Corneliu; Clima, Lilia; Marangoci, Narcisa; Danac, Ramona; Mangalagiu, Ionel I.; Simionescu, Bogdan C.; Pinteala, Mariana; Rotaru, Alexandru
Abstract : A novel supramolecular approach for the preparation of new non-toxic systems for staining cellular organelles is described. Abstract : The preparation and characterization of a supramolecular host–guest inclusion complex between a fluorescent indolizinyl-pyridinium salt and β-cyclodextrin is reported. The formation of the inclusion complex was investigated by ESI-MS experiments, transmission electron microscopy, Job's plot investigations and molecular docking studies, proving the formation of 1 : 1 and 1 : 2 species. Several interesting features of the investigated fluorescent indolizinyl-pyridinium salt/β-cyclodextrin inclusion complexes like the absence of cytotoxicity, cellular permeability, long-lived intracellular fluorescence and selective accumulation within acidic organelles made them remarkable candidates for the intracellular labelling of acidic organelles (lysosomes or mitochondria). Taking into account that a number of reported or commercially available cell staining dyes with low toxicity and solubility have already been used in cyclodextrin formulations with good results regarding the improvement of their properties, our results showed that this approach may also work with new and interesting toxic dyes capable of forming host–guest inclusion complexes with cyclodextrins.